2011
DOI: 10.1111/j.1476-5381.2011.01546.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological activation of KCa3.1/KCa2.3 channels produces endothelial hyperpolarization and lowers blood pressure in conscious dogs

Abstract: BACKGROUND AND PURPOSE In rodents, the endothelial KCa channels, KCa3.1 and KCa2.3, have been shown to play a crucial role in initiating endothelium‐derived hyperpolarizing factor (EDHF) vasodilator responses. However, it is not known to what extent these channels are involved in blood pressure regulation in large mammals, which would also allow us to address safety issues. We therefore characterized canine endothelial KCa3.1 and KCa2.3 functions and evaluated the effect of the KCa3.1/KCa2.3 activator SKA‐31 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 40 publications
5
70
2
Order By: Relevance
“…In a mouse model in which the expression level of SK Ca can be manipulated with dietary doxycycline, the amount of SK Ca expression in the EC was inversely correlated with the blood pressure . It is noteworthy that several studies in small and large animals demonstrated that activation of IK Ca and SK Ca channels using the drug SKA-31 could decrease blood pressure, making these channels a potential therapeutic target for treatment of hypertension (Sankaranarayanan et al, 2009;Hasenau et al, 2011;Damkjaer et al, 2012).…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 99%
“…In a mouse model in which the expression level of SK Ca can be manipulated with dietary doxycycline, the amount of SK Ca expression in the EC was inversely correlated with the blood pressure . It is noteworthy that several studies in small and large animals demonstrated that activation of IK Ca and SK Ca channels using the drug SKA-31 could decrease blood pressure, making these channels a potential therapeutic target for treatment of hypertension (Sankaranarayanan et al, 2009;Hasenau et al, 2011;Damkjaer et al, 2012).…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 99%
“…In dogs, i.v. injection of 2 mg/kg SKA-31 produced an immediate and strong (230 mmHg) but short-lived reduction in blood pressure (Damkjaer et al, 2012). In mice, SKA-31 doses of 10-30 mg/kg have been reported to lower blood pressure more prolonged (∼30 mmHg) for 60-90 minutes) (Sankaranarayanan et al, 2009;Köhler, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since both K Ca 3.1 and K Ca 2.3 are expressed in vascular endothelium and have been shown to be involved in the so-called endothelium-derived hyperpolarization (EDH) response Dalsgaard et al, 2010;Edwards et al, 2010;Köhler et al, 2010), SKA-31 was used as a pharmacologic tool to explore the role of K Ca channels in blood pressure regulation. While mice deficient in K Ca 3.1 and/or K Ca 2.3 exhibit impaired EDH responses and an increased mean arterial blood pressure (MAP) (Brahler et al, 2009), pharmacologic K Ca channel activation with SKA-31 lowered blood pressure in both mice and dogs (Sankaranarayanan et al, 2009;Damkjaer et al, 2012;Radtke et al, 2013). In dogs, i.v.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, opening SK Ca and IK Ca channels decreases myogenic tone, increases acetylcholine (ACh)-induced relaxation in rat cremaster arterioles (Sheng et al, 2009), and restores attenuated EDHF-type relaxation in mesenteric small arteries from Zucker diabetic fatty rats (Brøndum et al, 2010). Moreover, opening IK Ca channels decreases mean arterial blood pressure in angiotensin IIinduced hypertensive mice (Sankaranarayanan et al, 2009) and conscious dogs (Damkjaer et al, 2011). These results support findings that SK Ca and IK Ca channels are involved in controlling blood pressure and organ blood flow, and this often is attributed to EDHF-type relaxation.…”
Section: Introductionmentioning
confidence: 99%